Does oil price volatility affect the Malaysian stock market returns? evidence : 1980-2016 / Che Aira Nurshaitun Che Ku Ahmad - Che Ku Ahmad, Che Aira Nurshaitun (2020)
Based on the title of this study, “Does Oil Price Volatility Affect the Malaysian Stock Market Returns? Evidence: 1980-2016”, the researcher has decided to make oil price as a main independent variable for this study. This study is undertaken to study the oil price and macroeconomics variables towards the Malaysian stock market returns. The data employed in this study is from year 1980 until year 2016. This study is using Kuala Lumpur Composite Index (KLCI) as the dependent variable. Independent variables used in this study are oil price, money supply, interest rate and exchange rate. This study used Ordinary Least Squares, Correlation Matrix, Unit Root Test by Augmented Dickey Fuller (ADF) Test & Phillip Parrons (PP) Test, Cointegration Test and Long-run coefficient. It is found that money supply and interest rate are statistically significant in determining the Malaysian stock market returns. Meanwhile, oil price and exchange rate are found to have a negative relationship with Malaysian stock market returns. From the result, there is no multicollinearity problem exist between independent variables.